PROFESSIONAL TRANSLATOR CERTIFICATION: IMPLICATIONS FOR ASSESSMENT IN UNDERGRADUATE PHILOLOGISTS’ TRAINING - KOROL, Tetiana (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2020)
The problem of compatibility and competitiveness of domestic university graduates on globalized labour market is gaining momentum nowadays and appears to be of great topicality in terms of prospective philologists’ university training. Since they are expected to provide professional translation and intermediary services in different domains enabling effective cross-cultural and interlingual communication. That is why, the content of their training programs should be revised on the basis of market-oriented trends and requirements. This revision should be reflected in the list of their learning outcomes, in general, and in the assessment system, in particular. Assessment as the key component of any training system should bridge the gap between instruction and professional practice. The latter one is represented in different national and international translation & interpretation standards and certification frameworks. Therefore, the purpose of the given article is to compare relevant translator certification examinations that can be treated as the reliable source of professionally grounded information on the potential assessment objects and expected level of their acquisition, evaluation tools, methods and criteria, which should be taken into account while developing assessment system for prospective philologists’ training in Ukrainian universities. To this end, we have selected and compared three foreign certification frameworks of ATA (American Translator Association), CTTIC (Canadian Translators, Terminologists and Interpreters Council), and NAATI (Australian National Accreditation Authority for Translators & Interpreters). The main selection criteria included option of translator certification in general domain and English–Ukrainian language combination availability consistent with undergraduate philologists’ training curriculum in Ukraine. These frameworks were analysed in terms of general issues, examination format and procedures, and grading method. The received results were interpreted regarding their implications for domestic assessment system optimization in undergraduate philologists’ education